Rhoda Fleming $1 (BVolume 4s - Meredith, George, 1828-1909 (Salt Lake City, UT : Project Gutenberg, 2003)
"Rhoda Fleming $1 (BVolume 4" by George Meredith is a novel written in the late 19th century. It explores the complexities of human relationships and social dynamics, particularly focusing on the lives of its key characters, Robert and Dahlia. The narrative delves into themes of love, betrayal, and redemption as the characters navigate their interwoven existences against a backdrop of societal expectations. At the start of the fourth volume, the tension between characters is palpable. Robert and Major Waring engage in a conversation reflecting on social standings and alliances, particularly regarding the questionable association between the gentleman Algernon Blancove and the dubious Sedgett. Concurrently, the story introduces Dahlia, who grapples with her own troubled past and the burden of her choices. The opening draws readers into the emotional struggle of these characters, setting the stage for a deeper exploration of personal redemption and the pursuit of acceptance in a changing social landscape. (This is an automatically generated summary.)s
Release date is 2003-09-01
This etext was produced by Pat Castevans and David Widger
Keywords: Great Britain -- Social life and customs -- 19th century -- Fiction; Farm life -- Fiction; English fiction -- 19th century; Middle class -- Fiction